The Contribution of Intercessory Prayer in the Growth of the Early Church According to the Book of Acts - Bolean Silalahi (International Journal of Science and Society, 2021)
The Contribution of Intercessory Prayer in the Growth of the Early Church according to the Book of the Acts provide a great role and influence for the growth and development of the Church. The Church as a Spiritual Organization craves healthy growth and development, both in quality and quantity. One of the most effective and efficient ways is to intercede, in addition to other methods of course. Nowadays, Intercessory prayer is receiving less serious attention in some churches. The growth and development of the Gospels according to what is written in the Book of Acts shows an event that resulted in major and prominent changes to be examined. There is a significant growth in the preaching of the Gospel both in terms of quality and quantity, many prayers delivered to God are fulfilled and accomplished. In the development of Mission and Gospel in this world it cannot be denied that there are certain individuals, even certain groups do not agree that the creation of a Church growth and development is caused by one of the supporting factors, namely Intercessory Prayer. Luke the writer of the Book of Acts reveals the extraordinary events experienced by Jesus's disciples. The outpouring of the Holy Spirit became the basis of everything that happened and the disciples obeyed the commandments. Behind these events there is a very important thing to remember, that they gather and pray, and even intercede for the fulfillment of God's promises for them and the world. Disciples are baptized, equipped, and even empowered by the Holy Spirit to carry out the Great Commission of Jesus Christ. There is no denying that this miraculous event in the Book of Acts has had a great impact until now. Because through this event many people became believers in Jesus Christ and accepted the Gospel in their lives. So that the Church is growing rapidly and extraordinary. Everything that happened during the Early Church was the key to the growth and development of the Church today. May Churches today increasingly realize that behind the Intercessory Prayer there is a real power that will be fulfilled by God for His people. Especially at this time of the Pandemic Covid-19, Intercessory Prayer is very urgent and important because the Churches needed the power of the Holy Spirit poured out for the Churches in this world.